Pengembangan Media Komik Berbasis Kearifan Lokal untuk Menentukan Pesan dalam Dongeng pada Siswa Sekolah Dasar - Suwarti, Suwarti; Laila, Alfi; Permana, Erwin Putera (Profesi Pendidikan Dasar, 2020)
This study aims to; (1) do need assesment of students and teachers for the development of learning media in form of comic; (2) do validation by media experts, material experts, and language experts; (3) examine the effectiveness of the developed comic toward enhancement of the ability to decipher messages in fairy tales. This research and development applied ADDIE Analysis, Design, Develop, Implement, Evaluate) model. The population of this study is 3rd grade students of SDN Sukorame 2 Elementary School. Data collection methods by observation, interview, questionnaire and documentation. Evaluation of the validity of instructional media involved of five material experts and media experts. The result of this study find: (1) Teachers and students need the development of comic based on local wisdom. (2) The validation score by the material expert is 89%, by the media expert is 82%, and by the language expert is 84.44%. (3) The effectiveness of developed comic can be seen from the questionnaire and pre-post test result. The pretest score is 68 and the posttest score is 84. Meanwhile the teacher questionnaire score is 92% and student questionnaire score is 93.75%. Based on these results, the comic developed is needed for students and teachers, very valid, and very effective.